Digital Business, Frugal Innovation, and Firm Performance by Small and Medium-sized Enterprises in Developing Countries: Evidence from Indonesia - David Tjahjana, Adler Haymans Manurung, Wibowo Kosasih, Nugroho Juli Setiadi (International Journal of Advanced Science and Technology, 2020)
Researchers have considered the Indonesian problem, revealing that the Digital Islands of Indonesia are the most significant online user base in the region of Southeast Asia (150 million internet users in 2018). Indonesians spend about four hours on average on the internet daily. Indonesia has the most significant online economy (twenty-seven billion dollars in 2018) and the fastest growing online economic climate in Southeast Asia. Nevertheless, usage of e-commerce itself in small and medium-sized companies in Indonesia remains between 9 and 15%. One of the innovation types that this study looked at was frugal innovation, which can be defined as products, services, or solutions that arise regardless of financial, human, technological or other resource constraints, and where the end result is cheaper than competitive offers and meets the needs of customers who have not yet been served otherwise. The purpose of this research is to investigate the impact of digital business adoption, organizational innovation, and frugal innovation on firm performance. The study was conducted in Indonesia using a descriptive quantitative method. A structured research questionnaire was developed using a Likert scale of four points. Data from a total of 100 returned questionnaires was analysed with SEM-PLS. The results of this research show how the performance of small and medium-sized enterprises (SMEs)in Indonesia is affected by digital business adoption, organisational innovation and frugal innovation.